Prenatal development of the oviduct in goat - Harshan, K R; Singh, Yashwant; Sharma, D N (The Indian Journal of Animal Sciences, 2012)
The prenatal development of the oviduct in the goat was studied using 72 normal embryos. Oviducts developed from the primitive Mullerian ducts. At first they appeared as the Mullerian groove on the antero-ventral aspect of the mesonephros in 8 mm embryos. A lumen lined by columnar cells was formed in 35 mm embryos. Condensation of mesenchyme around the duct was noticed in 50 mm embryos. Circular muscle coat differentiated in 200 mm embryos and all the 3 tunics were very well developed in 200 mm subjects.